2010
DOI: 10.3368/er.28.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Linking Geomorphological and Ecological Responses in Restored Urban Pool-Riffle Streams

Abstract: Little attention has been focused on evaluating river restoration projects. Postproject assessments commonly identify improvements in biological or physical conditions, but opportunities for understanding the interactions between such processes are often missed. This study assesses the linkages between geomorphological and ecological responses in three stream channels in Austin, Texas, restored since 1998 with riffles and steps and riparian planting along graded banks. Prerestoration topographic surveys and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Some studies have studied its effect of restoration, for example, Shieds et al [2] studied the effect of ELD on fish species, and the results showed that the ELD can restore the river habitat complexity and enhance fish species. Chin et al [3] used the benthic macroinvertebrates as indicators to investigate the effect of ELD in an urban stream. Negishi and Richardson [4] studied the organic matter and macorinvertebrate response to place of boulder clusters in a small stream, and find that ELD can enhance the amount of organic matter and macrinvertebrate.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have studied its effect of restoration, for example, Shieds et al [2] studied the effect of ELD on fish species, and the results showed that the ELD can restore the river habitat complexity and enhance fish species. Chin et al [3] used the benthic macroinvertebrates as indicators to investigate the effect of ELD in an urban stream. Negishi and Richardson [4] studied the organic matter and macorinvertebrate response to place of boulder clusters in a small stream, and find that ELD can enhance the amount of organic matter and macrinvertebrate.…”
Section: Introductionmentioning
confidence: 99%